(untitled) (African Journal of Biomedical Research, 2024)
The present study investigated the ameliorative effects of Vitamin C (Vit. C) and N-acetylcysteine (NAC) on mercury chloride (HgCl2)-induced neurotoxicity in male Wistar rats. Twenty (20) male Wistar rats were randomly grouped into four, n=5. I: control, received 0.5mL normal saline, II: received HgCl2 alone (5mg/kg), III: received HgCl2 (5mg/kg) plus Vit. C (100 mg/kg), IV: received HgCl2 (5mg/kg) and N-acetylcysteine (NAC) (50mg/kg) for fourteen (14) days. All the drugs were administered orally. The rats were subjected to behavioural tests (Morris water maze, novel object recognition, light and dark box, fore limb grip strength and beam walking balance tests). The rats were then euthanized to obtain brain tissues for the determination of catalase activity, total protein and nitric oxide (NO) levels. The result revealed a significant (P<0.05) increase in the escape latency, beam walking latency, and footslip scores, and a significant (P<0.05) decrease in the recognition ratio, exploration frequency, and drop-off time in the rats that were exposed to HgCl2 only. However, Vit. C and NAC reversed the observed behavioural deficits. Similarly, HgCl2 exposure caused a significant (P<0.05) decrease in the brain catalase and total protein, and a significant (P<0.05) increase in the NO level. Also, administration of Vit. C and NAC significantly (P<0.05) reversed the trend. This study concludes that Vit. C and NAC ameliorated HgCl2-induced neurotoxicity via attenuation of behavioural deficits and oxidative stress